The biogeography of alien plant invasions in the Mediterranean Basin. (15th March 2021) - Cao Pinna, Luigi; Axmanová, Irena; Chytrý, Milan; Malavasi, Marco; Acosta, Alicia T. R.; Giulio, Silvia; Attorre, Fabio; Bergmeier, Erwin; Biurrun, Idoia; Campos, Juan Antonio; Font, Xavier; Küzmič, Filip; et al.
Abstract: Aims: Humans have deeply eroded biogeographic barriers, causing a rapid spread of alien species across biomes. The Mediterranean Basin is a biodiversity hotspot but is also known as a hub of alien plant invasions, particularly in its European part. Yet, a comprehensive inventory of alien species in the area is missing and understanding of the drivers of Mediterranean invasions is poor. Here, we aim to identify the main alien plant species in the European part of the Mediterranean Basin and quantify their invasion success in order to understand the plant species flows from other biomes of the world. Location: The Mediterranean region of Europe, Anatolia and Cyprus. Methods: We analyzed 130, 000 georeferenced vegetation plots from the European Vegetation Archive (EVA) and identified 299 extra‐European alien plant species. We identified their biomes of origin and quantified the mean geographic distance, trade exchange and climatic similarity from each biome to the study area. After estimating the invasion success of each species in the study area, we tested which biomes have donated more alien species than expected by chance and which drivers best explain these non‐random patterns. Results: We found that other Mediterranean climatic regions, as well as temperate and xeric biomes of the world, are the main donors of successful alien species to Mediterranean Europe, beyond what would be expected by chance. Our results suggest that climatic matching, rather than geographic proximity or trade, has been the most important driver of invasion. However, climatic pre‐adaptation alone also does not appear to predict the invasion success of established species in the study area. Conclusions: Our results highlight the need to pay special attention to alien plant species from the same or climatically similar biomes, but also suggest that further research is needed for early screening of the most problematic alien species. Abstract : We traced alien species flows toward Mediterranean Europe from other biomes of the world and asked which invasion drivers are most important. Our results showed that climate matching best explains invasions in the Mediterranean, indicating that the pre‐adaptations of species to similar conditions promote invasions more than trade routes or geographical distance.